Use of Simulation in Medical Education - Salam, Abdus; Akter, Shaima; Salam, Md Mushtahid; Taher, Salaheldin; Moftah, Abdulhameed Gadmor; Pasha, Mehboob Alam; Begum, Hamida; Satwi, Sapari; Zakaria, Hasbullani (International Journal of Human and Health Sciences (IJHHS), 2024)
Abstract not available International Journal of Human and Health Sciences Vol. 08 No. 02 Apr’24 Page: 111-115